Autosomal dominant simple microphthalmos. Issue 9 (September 1994) - Vingolo, E M; Steindl, K; Forte, R; Zompatori, L; Iannaccone, A; Sciarra, A; Del Porto, G; Pannarale, M R
Abstract : Congenital bilateral microphthalmos is a rare malformation of the eye, which ranges from extreme to mild reduction of total axial length. Microphthalmos may occur as an isolated ocular abnormality or as part of a systemic disorder, and different classifications of the condition have been attempted. We describe a large pedigree with 14 persons in four generations affected with bilateral microphthalmos without other ocular or systemic signs. An autosomal dominant trait with complete penetrance is proposed. Five subjects underwent a complete ophthalmological evaluation. The total axial length was measured by A scan ultrasonography in all persons. Ultrasonography showed a reduction of the total axial length (range 18.4-19.7 mm) and a reduced vitreous cavity length (range 11.4-13.5 mm) in all investigated patients. All the patients had microcornea (range 8-9.7 mm). No other ocular anomalies or associated systemic malformations were found. A review of published reports also suggests that simple, partial, posterior, pure microphthalmos and nanophthalmos are similar clinical entities sharing total axial length and vitreous cavity length reduction. Therefore, the term simple microphthalmos is proposed to identify these clinical conditions.